Improving Sustainable Financing for Universal Health Coverage in Bhutan: Exploring Policy Options and Financial Strategies - Ugyen Tshering; Jayendra Sharma; Dorji Tshering; Tandin Dendup (Wiley, 2024)
Abstract Deeply rooted in its developmental philosophy of gross national happiness (GNH), Bhutan's healthcare system strives towards achieving a shared goal of universal health coverage (UHC). Despite being primarily financed by the government, the health system faces a plethora of challenges. To overcome these hurdles and achieve UHC goals, expanding the fiscal space for health and improving operational efficiency are crucial. This article aims to address Bhutan's evolving healthcare landscape and advance the achievement of UHC through two policy options. The first policy option focuses on the dual objective of improving health outcomes and promoting financial sustainability by leveraging health taxes, whereas the second option emphasizes reinforcing a systematic health technology assessment (HTA) in the Bhutanese health system. First, drawing lessons from global experiences, the policy brief recommends leveraging health taxes to reduce societal and healthcare costs and enhance financial sustainability in the health sector. Considering Bhutan's high prevalence of tobacco and alcohol consumption, and taking opportunity from the ongoing Goods and Services Tax (GST) reform, continued advocacy on health taxes is essential, and soft earmarking the health taxes may be considered to finance a broader array of public health programmes, particularly focusing on the promotion of healthy lifestyle, health screening and outreach public health activities. Second, the integration of HTA into policymaking and decision‐making processes is essential for effective resource allocation in UHC. Nurturing and strengthening the existing HTA governance structure under the Ministry of Health (MoH) and establishing a dedicated multidisciplinary HTA Committee will ensure informed decision‐making and resource optimization. HTA evidence should inform the revision of health service standards, clinical guidelines development, procurement decisions and healthcare priorities. These policy options can assist the country in improving financial sustainability, enhancing effective resource allocation and utilization and improving healthcare delivery, aligning with its vision of GNH and ultimately accelerating progress towards achieving UHC.